Pasta Gigi Lidah Buaya (Aloe vera) sebagai Alternatif Herbal Untuk Kesehatan Gigi dan Mulut - Sarah Nabila Wiguna; Murniwati Murniwati; Kosno Suprianto (Faculty of Dentistry Universitas Andalas, 2022)
Background: Dental and oral health have an important role on overall body health, because it can affect someone's physical and psychological condition. The common tooth and mouth disease is periodontal disease. The main cause of periodontal disease is due to the presence of colonizing microorganisms in dental plaque. Gingivitis is a periodontal disease that is commonly found in the community. Review: Aloe vera as an herbal plant has many benefits because of its properties, such as; antiseptic, antioxidant, anti-inflammatory, analgesic, antimicrobial, and wound healing. Purpose: The purpose of this literature review is to identify the potential use of Aloe vera toothpaste as an herbal alternative for oral health. Conclusion: Toothpaste containing Aloe vera has been shown to inhibit plaque formation, due to its saponin compound. Aloe vera toothpaste can also significantly reduce the gingival index.